Effect of Co‐Surfactants on Properties and Bactericidal Activity of Cu2O and Hybrid Cu2O/Ag Particles - Dam Xuan Thang; Nguyen Thuy Chinh; Nguyen Thi Binh Minh; Trinh Hoang Nghia; Thai Hoang (ChemistryOpen, 2024)
Abstract Nanomaterials based on metal oxides, especially Cu2O, have received much attention in recent years due to the many unique properties of the surface plasmon resonance they provide. The report presented the co‐precipitation method, a simple preparation method to produce Cu2O oxide particles. In addition, to improve the unique antibacterial properties of Cu2O, a proposed method is to attach Ag nanoparticles to the surface of Cu2O particles. The Cu2O and Cu2O−Ag particles were synthesized based on redox reactions using ascorbic acid (LAA) as a reducing agent. Moreover, in this experiment, two surfactants, polyethylene glycol 6000 (PEG 6000) and sodium dodecyl sulfate (SDS), were added during the manufacturing process to create particle samples and particle combinations with better properties than the original sample. Changes in the characteristics and properties of particle samples are determined by many different physical and chemical methods such as ultraviolet‐visible spectroscopy (UV‐Vis), infrared spectroscopy (IR), noise X‐ray radiation (XRD), scanning electron microscope (SEM), dynamic light scattering (DLS), energy dispersive X‐ray spectroscopy (EDS), and transmission electron microscopy (TEM). Finally, the activity against bacteria, including E. coli and S. aureus, was also tested using the agar well diffusion method to determine the zone of inhibition. The results improved the particle size value, which decreased by half to 200 nm when two additional surfactants, PEG and SDS, were added. In addition, the antibacterial ability has also been shown to increase significantly when the diameter of the bacterial inhibition zone increased significantly, reaching values of 20 mm (Cu2O/Ag/SDS) and 32 mm (Cu2O/Ag/PEG) for the E. coli bacterial strain. The initial test sample was only about 14 mm in size. The S. aureus bacterial strain also had a similar improvement trend after adding Ag to the Cu2O surface with the appearance of two surfactants, SDS and PEG. The inhibition zone diameter values reached the optimal value at 36 mm in the Cu2O/Ag/PEG particle combination sample compared to only the initial 26 mm in the Cu2O particle sample. Finally, the particle samples are added to the acrylic emulsion paint film to evaluate the changes. Positive results were obtained, such as improvement in adhesion (1.22 MPa), relative hardness (240/425), and sand drop resistance (100 L/mil) in the Cu2O/Ag/PEG particle combination sample, which showed the correctness and accuracy of the research.